Travel down the river: The subfluvial tunnel Paraná - Santa Fe (1969): engineering and architecture connecting territories - Costa, Camila (Universidad ORT Uruguay, 2020)
In 1960, two Argentinian provinces (Santa Fe and Entre Ríos) historically separated by the Paraná River, signed a treaty to build a subfluvial tunnel. This would definitively end the isolation of the Mesopotamian region in this country. Projected, built and inaugurated (1969) within the framework of development policies, the “Uranga – Sylvestre Begnis” tunnel constitutes a technical, political and architectural milestone, as the result of an active State in the construction of the territory. In addition, just as the engineering scopes had enough merits to enter the history of great achievements, in architecture, high quality thresholds were also reached. This article aims to make visible the importance of the Subfluvial Tunnel in technical terms and highlight its architectural dimension. This is achieved by recognizing the performance of the studio of Mario Roberto Álvarez and associates as doers of the architecture that is integrated into what is ultimately an exceptional work, positioned in a prominent international level of disciplinary debate.